PENGARUH LEVERAGE, MEKANSIME GOOD CORPORATE GOVERNANCE, DAN IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Albert Manuel (2021)
This study aims to determine the impact of Leverage, Board of Directors, Independent Board of Commissioners, and Corporate Social Responsibility on the Company's Financial Performance in 24 Manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2019 period. This research is a quantitative research using secondary data in the form of annual reports and incident reports. In this study, a random effect (REM) model with panel data regression was used, using SPSS v26. Based on testing and analysis, it can be said that Leverage, Board of Directors, and Corporate Social Responsibility do not have a significant influence on the Company's Financial Performance. The results of this study also have further implications for companies, investors and researchers.